Dopamine D2-receptor Antagonist Droperidol Deepens Sevoflurane Anesthesia. (April 2018) - Araki, Ryuhei; Hayashi, Kazuko; Sawa, Teiji
Abstract : Background: Although midbrain dopaminergic pathways are known to contribute to arousal and emergence from anesthesia, few reports exist regarding the anesthetic effects of dopamine D2 receptor antagonism in humans. This study examined the effect of the D2 receptor antagonist droperidol on sevoflurane anesthesia by examining α and slow wave electroencephalogram oscillations. Methods: Forty-five patients, age 20 to 60 yr, were enrolled. Frontal electroencephalograms were continuously collected for offline analysis via Bispectral Index monitoring. After induction of anesthesia, end-tidal sevoflurane concentration was deliberately maintained at 1%, and intravenous droperidol (0.05 mg/kg bolus) was administered. Electroencephalogram changes were examined in power spectrum and bicoherence, before and 10 min after droperidol injection, then compared using the Wilcoxon signed-ranks test and/or paired t test. Results: Droperidol significantly augmented the α-bicoherence peak induced by sevoflurane from 30.3% (24.2%, 42.4%) to 50.8% (41.7%, 55.2%) (median [25th, 75th percentiles]; P < 0.0001), Hodges-Lehman median difference, 15.8% (11.3 to 21.4%) (95% CI). The frequency of the α-bicoherence peak was simultaneously shifted to the lower frequency; from 11.5 (11.0, 13.0) to 10.5 (10.0, 11.0) Hz (median [25th, 75th percentiles], P < 0.0001). Averaged bicoherence in the δ-θ area increased conspicuously from 17.2% (15.6 to 18.7%) to 25.1% (23.0 to 27.3%) (mean [95% CI]; P < 0.0001), difference, 8.0% (6.0 to 9.9%). Conclusions: Droperidol augments both α and δ-θ bicoherences while shifting the α-bicoherence peaks to lower frequencies, and enhances the effect of sevoflurane anesthesia on the electroencephalogram via γ-aminobutyric acid–mediated oscillatory network regulation. Abstract : Administration of droperidol decreased Bispectral Index values, augmented both α and δ-θ bicoherences, and shifted α-bicoherence to lower frequencies. These data suggest that droperidol enhances sevoflurane's effect on the electroencephalogram, partly via γ-aminobutyric acid–mediated subcortical reverberating networks.